Public Participation and Rural Development in South Chhindwara forest Division, Chhindwara (madhya Pradesh) - Ahmad, Shahbaz (Indian Forester, 1994)
The achievements of rural development programmes conducted through Public Participation in South Chhindwara Forest Division, Chhindwara, Madhya Pradesh have been described in detail.